Phase field modeling of heterogeneous microcrystalline ceramics. (July 2019) - Clayton, J.D.; Leavy, R.B.; Knap, J.
Abstract: Diffuse interface models and simulations capture deformation and failure of polycrystalline ceramics with multiple phases. Two heterogeneous ceramic solids are investigated. The first consists of a boron carbide matrix phase embedded with titanium diboride grains. Boron carbide may undergo cleavage fracture, twinning, and amorphization under sufficient mechanical loading. Titanium diboride demonstrates cleavage fracture and limited plastic slip. The second ceramic composite consists of diamond crystals with a smaller fraction of silicon carbide grains, where the latter may encapsulate the former in a micro- or nano-crystalline matrix and/or may be interspersed as larger micro-crystals among the diamond grains. Diamond may undergo cleavage fracture while the cubic phase of silicon carbide may fracture and twin. A general constitutive framework suitable for representing behaviors of all phases of each material system is reported. This phase field framework is implemented in three-dimensional (3D) finite element (FE) simulations of polycrystalline aggregates under compressive loading. Numerical results demonstrate effects of grain and phase morphology and activation or suppression of slip or twinning mechanisms on the overall strength and ductility of each material system. Efforts to inhibit localization and cleavage in boron carbide crystals, including addition of titanium diboride, promote increases in strength of the first composite, though residual stresses may be necessary to realize toughness improvements observed experimentally. In the second composite, layers of softer silicon carbide nanocrystals along grain boundaries (GBs) improve overall strength and ductility relative to addition of larger bulk silicon carbide grains.